Peran Sertifikasi Halal dalam Membangun Resiliensi Komunitas Muslim melalui Revitalisasi Kearifan Lokal - Rosyidah, Norma (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Halal certification is not just a label on a product but is also an essential instrument in strengthening Islamic identity and values in a multicultural society. This research explores how halal certification interacts with local wisdom to facilitate the internalization of Islamic values. Through case studies on several MSMEs, this research shows that halal certification influences consumption choices and encourages the revitalization of relevant local religious practices. Local wisdom, such as traditional knowledge about halal food ingredients, processing processes, and social justice values, acts as a bridge between universal Islamic values and the cultural context of society. Thus, halal certification is not only a product quality standard but also a catalyst for economic development based on Islamic values rooted in local wisdom.